A Questionnaire Based Study on Awareness of Sanitization of Tooth Brushes in Indian Population and Their Disinfection with an Oral Hygiene Aid Sterilizer: A Clinical and In-Vitro Study. (International Journal of Scientific Research and Management (IJSRM), 2024)
Abstract: Oral diseases are a major public health concern, owing to their high prevalence and their relationship with systemic health. Oral health maintenance can only be accomplished with proper tooth brushing & tongue cleaning. Toothbrushes are kept in places which is a hub of contaminants. They should be correctly stored, disinfected and changed at regular intervals. Aims: Our study focuses on awareness of disinfection of toothbrushes among general population and invention of a newer device that not only keeps the toothbrush moisture free but also germ free: Oral Hygiene Aid Sterilizer (OHA-S). Methods and Material: A cross sectional questionnaire based study of sample size 100 was conducted in which samples were randomly selected and distributed with a questionnaire form. All the study participants were asked to brush their teeth with the tooth brush provided. After brushing, the contaminated bristles were disinfected in the newer device: OHA-S and were observed under phase contrast microscope. Statistical analysis used: Randomized control trial Results: Survey results showed that 61% of general population was unaware of sanitization of toothbrushes. The remaining being aware, almost 72% did not perform sanitization on daily basis. Also, there was a significant decrease in microbial flora of the bristles which were sanitized using OHA-S when observed under the phase contrast microscope Conclusions: As majority of population failed at sanitizing oral hygiene aids daily, OHA-S was effective in not only making the oral hygiene aids moisture free but also in reducing the amount of microbial load which is the main causative factor for periodontal diseases .